EFFECTIVENESS OF APPLICATION OF MODERN MELIORATIVE TECHNIQUES IN CLEANING OF OPEN COLLECTORS AND DRINKS (Academicia Globe: Inderscience Research, 2021)
The proposed workplace is a new JY230ELD, one of the foreign equipment entering our country. It is used as an interchangeable workstation for JY230E excavator. The new excavator for use in agriculture construction consists of the following main components and other parts. Exacerbation of the global food problem increase agricultural production and is known to make land use more efficient. At the same time, land reclamation works and the use of the most modern equipment are becoming increasingly important.